Preventive Character Education Strategies against the Negative Impact of Social Media Influencers on the Betawi Alpha Generation - Evi Dalilah; Anastya Basyith Ad Dauwi; Ella Yanova; Mercynda Putri; Yohamintin Yohamintin (Cahaya Ilmu Cendekia Publisher, 2026)
Purpose of the study: This study focuses on the influence of social media influencers on Generation Alpha within the Betawi community, aiming to examine how digital media exposure shapes children’s moral values, communication ethics, and cultural identity in traditional societies facing rapid digital globalization. Methodology: This study employed a qualitative research methodology using a phenomenological approach to explore participants’ lived experiences and perspectives. Data were collected through in-depth interviews and participant observations conducted in several Betawi communities and schools. This approach enabled a comprehensive understanding of how influencer-driven digital content affects communication practices, behavioral norms, and the internalization of moral values within the Betawi socio-cultural context Main Findings: The findings indicate that exposure to influencer-generated content has contributed to shifts in moral reasoning, communication ethics, and cultural awareness among Generation Alpha. Children tend to adopt informal communication styles, reduced respect-based interaction patterns, and value orientations that differ from traditional Betawi norms. These changes are shaped by digital social environments, family mediation, and peer interactions, reflecting broader transformations in social behavior in the digital era. From a social studies perspective, these findings imply the need to integrate character education that emphasizes ethical communication, cultural literacy, and critical media awareness into learning practices. Social studies education can serve as a strategic space to strengthen students’ moral judgment and cultural identity amid ongoing digital influences Novelty/Originality of this study: This study offers originality by foregrounding the role of influencers and digital content creators in shaping character values, communication ethics, and cultural identity among Generation Alpha within a specific indigenous cultural context. By situating the analysis within Betawi society, the study contributes new insights into culturally grounded character education strategies in the field of social science education.